Integrating Digital Games-Based Language Learning for EFL Speaking Skills Development: A Case Study in an Indonesian University - Mustari, Sri Hariati; Noni, Nurdin; Salija, Kisman (English Education Department, 2024)
Digital learning has become a potential learning tool since the COVID pandemic which causes the use of new technologies including digital games-based language learning. However, the implementation still has challenges due to technical, instructional, and financial barriers. Previous studies suggest exploring more teaching experiences related to the use of digital games-based language learning for future contributions. This study aims to explore the implementation of digital games-based language learning in higher education. To achieve this goal, this study was conducted in an Indonesian higher education, the State University of Makassar by applying a qualitative case study to collect data. The researcher collected the data from 2 lecturers recruited using a convenient sampling technique. The thematic analysis was used to analyze the collected data. This study explores teacher experiences in using digital games-based language learning in a speaking classroom. This study found that the lecturers plan, implement, and evaluate digital games-based language learning in three categories namely well, moderate, and low implemented. From this result, it is claimed academically that digital games-based language learning (DGBLL) can be planned, implemented, and evaluated strategically in speaking classrooms based on learning objectives, learning outcomes, and students' learning needs. Combining technology with game-based learning, education can be more dynamic and relevant, accommodating a variety of learning styles and motivating students to be more actively involved in the learning process.